2020
DOI: 10.1021/acsami.0c06996
|View full text |Cite|
|
Sign up to set email alerts
|

Radiolabeling Strategies of Micron- and Submicron-Sized Core–Shell Carriers for In Vivo Studies

Abstract: Core–shell particles made of calcium carbonate and coated with biocompatible polymers using the Layer-by-Layer technique can be considered as a unique drug-delivery platform that enables us to load different therapeutic compounds, exhibits a high biocompatibility, and can integrate several stimuli-responsive mechanisms for drug release. However, before implementation for diagnostic or therapeutic purposes, such core–shell particles require a comprehensive in vivo evaluation in terms of physicochemical and phar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 67 publications
1
32
0
Order By: Relevance
“…Calcium carbonate particles represent a suitable carrier vehicle for various radionuclides. Successful labeling has been reported for the two alpha-emitting radionuclides 224 Ra ( t 1/2 = 3.6 days) and 225 Ac ( t 1/2 = 9.9 days), and for the positron emitters 89 Zr ( t 1/2 = 78.4 h) and 68 Ga ( t 1/2 = 67.7 min) [ 48 , 49 , 50 ]. Both 224 Ra and 225 Ac are relatively long-lived radionuclides compared to 212 Pb, which permits a longer production process and shelf-life of the labeled particles before the radiopharmaceutical reaches the end user.…”
Section: Discussionmentioning
confidence: 99%
“…Calcium carbonate particles represent a suitable carrier vehicle for various radionuclides. Successful labeling has been reported for the two alpha-emitting radionuclides 224 Ra ( t 1/2 = 3.6 days) and 225 Ac ( t 1/2 = 9.9 days), and for the positron emitters 89 Zr ( t 1/2 = 78.4 h) and 68 Ga ( t 1/2 = 67.7 min) [ 48 , 49 , 50 ]. Both 224 Ra and 225 Ac are relatively long-lived radionuclides compared to 212 Pb, which permits a longer production process and shelf-life of the labeled particles before the radiopharmaceutical reaches the end user.…”
Section: Discussionmentioning
confidence: 99%
“…Human serum albumin (HSA, V = 100 μL, c = 200 mg/mL) was diluted with 200 μL of deionized water, then it was added in 100 μL of saturated DTPA solution, and incubated at 37 °C for 30 min with subsequent ultrafiltration. Purified HSA was diluted in 0.1 M 4-(2-hydroxyethyl)-1-piperazineethanesulfonic acid (HEPES) buffer (pH 8.5) and conjugated with p SCN-Bn-DOTA or p SCN-Bn-DFO solution . The reaction was performed for 30 min at 37 °C and then for 24 h at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Calcium carbonate (CaCO 3 ) particles can be considered as a carrier to transport and hold 225 Ac and its daughter radioisotopes in the tumors. The fabrication of CaCO 3 -based carriers occurs in the coprecipitation reaction, allowing the incorporation of radiolabeled conjugates directly into the core of formed particles. , At the same time, the synthesis of CaCO 3 particles is a low cost, and the size and shape of the obtained particles can be tuned by varying the conditions of the coprecipitation reaction. In addition, CaCO 3 particles have wide possibilities of modification. For example, the surface of CaCO 3 particles can be modified with biocompatible polymers using the layer-by-layer (LbL) strategy. , It allows to improve their stability in biological fluids and enables multiple possibilities of loading with diagnostic and therapeutic agents. In our previous works, we developed the radiolabeling protocols of micrometric and submicrometric core–shell CaCO 3 particles and performed in vitro and in vivo studies, showing the validation of these particles to retain 225 Ac for the reduction of systemic toxicity. , Very recently, Kozlovskaya et al demonstrated the high potential of LbL carriers for positron emission tomography (PET) imaging . In other reports, Westrøm et al labeled uncoated CaCO 3 microparticles (3–5 μm) with a therapeutic radionuclide ( 224 Ra) and investigated their biodistribution in mice and therapeutic potential for the treatment of ovarian cancer …”
Section: Introductionmentioning
confidence: 99%
“…The versatility of LbL systems is also determined by a wide range of their modification possibilities that enable additional functionalities, such as light or magnetic field sensitivity, targeting abilities, catalytic or bioimaging properties, and others [26,27]. Similar to genetic material, organic or inorganic nanomaterials can be either incorporated between layers of polymers during the LbL procedure [28], or attached onto the surface of LbL particles [29], or loaded into the cavity of the LbL systems [30][31][32] (Figure 2(a)).…”
Section: Inorganic and Organic Nanostructures In Lbl Systems For Controlled Triggering And Manipulationmentioning
confidence: 99%
“…Although the LbL platform is still in its infancy and the data regarding the delivery of genetic material in vivo are limited, some important results were already demonstrated in preclinical studies of other LbL particles, which were stable in biological fluids and improved the pharmacokinetic profiles of the therapeutics as well as enhanced the safety and circulation halflife of the drug in vivo, proving a high clinical relevance of the platform [155,156]. By varying the particle diameter, and the charge and thickness of the LbL capsule wall, the distribution of the carriers in vivo may be tuned with control over the cargo release rate, depending on the specific aims [32]. As an example, delivery of capsules to the liver was demonstrated [157], which may be important for enzyme replacement gene therapy for various metabolic disorders [158].…”
Section: In Vivo Gene Therapymentioning
confidence: 99%